Comparison of Findings of Fine Needle Aspiration Cytology and Histopathological Examination of Thyroid Swelling - Naha, Abirvab; Rahman, Mohammad Habibur; Biswas, Ashim Kumar; Saha, Joyosree; Rahaman, HM Mustafizur; Haque, Hasanul (Bangladesh Journal of Otorhinolaryngology, 2024)
Background: Thyroid swellings are very common nowadays. To evaluate the nature of a thyroid disease FNAC is considered as the gold standard diagnostic tool. It plays a key role in determining the treatment plan and its cost-effectiveness makes it more popular. An accurate result in a short period makes FNAC more reliable. Objectives: The purpose of this study is to compare the FNAC results with the final histopathological diagnosis to determine the accuracy of the diagnosis of thyroid neoplasm based on FNAC results. Methods: In this study, a total of 100 patients presenting with thyroid swelling or nodules underwent FNAC with subsequent surgery from January 2022 to December 2022 at Green Life Hospital. Cytological diagnosis was classified according to the Bethesda classification. Final histopathological results were compared to find out the accuracy of FNAC. Results: Of 100 patients with a thyroid nodule or swelling, 74 (74%) were women and 26 (26%) were men between 21 to 70 years of age. On FNAC, we found 70 cases of benign and 30 cases of malignant. After Histopathological examination, we found 58 cases of benign and 42 cases of malignant. The sensitivity and specificity are 64.28% and 94.82%. The accuracy of FNAC in the diagnosis of benign or malignant thyroid lesions was 82%. Conclusions: FNAC is verypopular, safe, simple, rapid, and cost-effective. It is a minimally invasive procedure. An accurate and reliable cytology report may help to reduce unnecessary surgery in patients with benign thyroid. Bangladesh J Otorhinolaryngology 2023; 29(2): 104-111